Pengaruh Harga Emas Dan Minyak Dunia Terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2016-2019 - ABDUL BASIT (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
The purpose of this study was to determine the effect of world gold and oil prices on the 2016-2019 period composite stock price index (IHSG). This research is a quantitative study with panel funds regression estimation (time series). This study uses secondary data types in the form of gold, world oil and IHSG prices. This data analysis technique uses multiple linear regression analysis. Based on the analysis results it can be explained that the partial test / t-test statistic shows that the gold price variable has no influence on the 2016-2019 IHSG period. While world oil has an influence on the 2016-2019 IHSG. The F Test results can be explained that simultaneously the world gold and world oil price variables have an influence on the 2016-2019 IHSG period. From the results of the test of the coefficient of determination can be found that the variable world price of gold and oil can affect the CSPI by 75%.